Influence des facteurs climatiques sur la production conchylicole du bassin de Marennes-Oléron - Heral, Maurice; Prou, Jean; Deslous-paoli, Jean-marc (Société Française de Malacololgie, 1986)
The authors are comparing the recruitment, the commercialised production, the cultivated biomasses of oysters Crassostrea gigas and Crassostrea angulata with the statistics of the meteorology (1885-1984). The temperature plays a role up on the date of spawning but partialy explains the lack of recruitment, which has less impact on the commercialised production than on the total biomass. The annual and seasonal characteristics of the precipitations and water temperatures do not show tight correlations with the variations of the production and of the biomass, for these cultivated populations in opposition with the sensitivity of the natural molluscan populations towards the climatic factors. Les auteurs mettent en relation le recrutement, les productions commercialisées, les stocks en élevage des huîtres Crassostrea gigas et Crassostrea angulata avec les statistiques de la météorologie Nationale pour les années correspondantes : 1885-1984. La température agit sur la date de ponte mais n'explique que partiellement les défauts de recrutement qui présentent moins d'impact sur la production commercialisée que sur le stock d'huîtres. Les caractéristiques annuelles et saisonnières des précipitations et des températures de l'air ne montrent pas de corrélations étroites avec les variations de la production et du stock pour ces populations cultivées contrairement à la sensibilité des populations naturelles de mollusques vis à vis des facteurs climatiques.